Interleukin-17 directly stimulates tumor infiltrating Tregs to prevent cancer development - Theune, William C.; Chen, Ju; Theune, Eileen Victoria; Ye, Xiaoyang; Ménoret, Antoine; Vella, Anthony T.; Wang, Kepeng (Frontiers in Immunology, 2024)
Background: Interleukin-17 (IL-17) family cytokines promote protective inflammation for pathogen resistance, but also facilitate autoimmunity and tumor development. A direct signal of IL-17 to regulatory T cells (Tregs) has not been reported and may help explain these dichotomous responses. Methods: We generated a conditional knockout of Il17ra in Tregs by crossing Cdx2-YFP-Cre mice to Il17ra-flox mice (Il17raΔTreg mice). Subsequently, we adoptively transferred bone marrow cells from Il17raΔTreg mice to a mouse model of sporadic colorectal cancer (Cdx2-Cre+/ApcF/+), to selectively ablate IL-17 direct signaling on Tregs in colorectal cancer. Single cell RNA sequencing and bulk RNA sequencing were performed on purified Tregs from mouse colorectal tumors, and compared to those of human tumor infiltrating Treg cells. Results: IL-17 Receptor A (IL-17RA) is expressed in Tregs that reside in mouse mesenteric lymph nodes and colon tumors. Ablation of IL-17RA, specifically in Tregs, resulted in increased Th17 cells, and exacerbated tumor development. Mechanistically, tumor-infiltrating Tregs exhibit a unique gene signature that is linked to their activation, maturation, and suppression function, and this signature is in part supported by the direct signaling of IL-17 to Tregs. To study pathways of Treg programming, we found that loss of IL-17RA in tumor Tregs resulted in reduced RNA splicing, and downregulation of several RNA binding proteins that are known to regulate alternative splicing and promote Treg function. Conclusion: IL-17 directly signals to Tregs and promotes their maturation and function. This signaling pathway constitutes a negative feedback loop that controls cancer-promoting inflammation in CRC.